Answer:
I think it is 8, i did not learn this in school
Step-by-step explanation:
2(3x^2+5)
6x^2+10
Answer:
see explanation
Step-by-step explanation:
(a)
Given
x² + 5x + 6
Consider the factors of the constant term ( + 6) which sum to give the coefficient of the x- term ( + 5)
The factors are 3 and 2, since
3 × 2 = 6 and 3 + 2 = 5, hence
x² + 5x + 6 = (x + 3)(x + 2) ← in factored form
(b)
To solve
x² + 5x + 6 = 0 ← use the factored form, that is
(x + 3)(x + 2) = 0
Equate each factor to zero and solve for x
x + 3 = 0 ⇒ x = - 3
x + 2 = 0 ⇒ x = - 2
1 person = 130 + (60x7) + 350 = 900
4 people = 4 x 900 = 3600
I think this is right !
Answer:
x=45
Step-by-step explanation:
70+65=135
180-135=45